Randia aculeata White Indigoberry: FPS497/FP497, 6/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of Randia aculeata, commonly known as white indigoberry. It describes the plant’s characteristics, including its height, spread, leaf arrangement, and flowering habits. The shrub is noted for its fragrant white flowers and white fruits, which attract birds. It thrives in well-drained sandy or rocky soils, is highly drought-tolerant, and has a high salt spray tolerance, making it suitable for coastal landscapes. The document also highlights its uses in landscaping, such as a specimen plant, foundation, or border shrub, and mentions its general pest resistance and non-invasive nature. Original publication date October, 1999.